One nation under Graham: apocalyptic rhetoric and American exceptionalism - Redding, Jonathan D. (Baylor University Press, 2021)
"Examines the influence of Billy Graham's interpretations of Daniel and Revelation in connection with the inclusion of "under God" in the USA's Pledge of Allegiance, a move that continues to affect contemporary laws and legislation"--